A pie-like structure double-sidedly assembled with ZnO-nanodisks vertically on Cu-nanoplates and its photochemical properties. (November 2020) - Wang, Yi; Xu, Hongwu; Zan, Guangtao; Wu, Tong; Wu, Qingsheng
Abstract: A novel pie-like structure of vertically stacked ZnO-nanodisks on Cu-nanoplates interlayer is prepared for the first time by a facile synthesis. The photochemical activity of the as-prepared samples was evaluated by the degradation of Rhodamine B (RhB) under UV-light. Because of the formation of heterojunction and closely-bonded layered structure, the novel nanocomposites can restrain the recombination of charge carriers and have better collection ability of light. The photocatalytic experiments show that the composites are 258% of the catalytic activity of pure ZnO-nanodisks prepared by the same method, and the target pollutant RhB was almost completely degraded (96.5%) within only 10 mins. The novel Cu-nanoplates/ZnO-nanodisks assembled materials with greatly promoted performance are of significant interest for chemical and environmental applications. Highlights: We choose Cu, as metal substrate, to design a pie-like structure photocatalyst. The photocatalyst formed heterojunction and better utilized of light energy. The composite has promoted photochemical performance which is 258% of the pure ZnO. The target pollutant RhB was almost degraded (96.5%) within only 10 min.